Digital Subtraction Radiography in Dentistry: An Overview: Life Sciences- Radiology - R. Sonar, Dr. Prasanna; S. Panchbhai, Dr. Aarati (International Journal of Life Science and Pharma Research, 2023)
Digital imaging has transformed the field of medical and dental imaging by overcoming many of the drawbacks ofconventional film-based radiographs. These alterations, however, are hidden behind a background of typical anatomical featuresand are not readily visible, making it difficult for the human eye to discern them. One image-enhancing method or tool that solvesthis issue is digital subtraction radiography, which has recently found usage in a number of dental specialties. Quantitative measuresfrom digital subtraction pictures have been validated as a result of the development of digital imaging technology. Moreover,changes made to computer software have made the clinical use of subtraction imaging more adaptable. Digital subtraction radiologyhas significantly improved the ability to find oral and maxillofacial lesions. Comparing standardised radiographs acquired duringsuccessive examination sessions is done using digital subtraction radiography. Any structures that have not changed are removed,and these regions are shown in the subtraction picture as neutral grey areas, whilst parts that have altered are shown as deeperor brighter shades of grey. Yet, there is not much analysis of this often used method in the literature. The purpose of this articleis to examine this technology, its applications in different areas of dentistry, and its potential for detecting a range of disorders.This review article highlights its basic principles, applications, technique, advantages, disadvantages and future scope of digitalsubtraction radiography in dentistry.